Creep behavior of PLA‐based biodegradable plastic exposed to a hydrocarbon liquid. Issue 4 (16th May 2012) - Widiastuti, Indah; Sbarski, Igor; Masood, S.H.
Abstract: This study explores the effect of hydrocarbon liquid on creep behavior of polylactic acid (PLA)‐based plastic. Evolution of the mechanical properties of the material was investigated experimentally by measurement of creep under tensile load. Tensile creep behavior was studied with a constant load over a temperature range from 30 to 50°C using specimens containing different levels of liquid. It was shown that the hydrocarbon liquid diffusion obeys the Fickian law of diffusion. The viscoelastic properties vary with temperature and these properties dramatically decrease above the glass transition temperature ( T g ). Significant decreases in modulus and in the peak of tan δ were observed with an increase in liquid concentration at low temperatures. In contrast, at high temperatures, drier material recorded lower storage modulus. However, only small changes of T g were recorded. Dependence of compliance on temperature was observed in the creep test at all levels of liquid content. With respect to drier samples, it was noted that the high liquid content material had a lower rate of increasing creep strain with temperature. Therefore, at elevated temperatures, higher creep strain of dry specimens was observed compared to those with a higher liquid content. The improvement of creep resistance and stiffening of material at high temperatures can be attributed to the significant increase of crystallinity fraction induced by liquid absorption. Understanding the effect of liquid diffusion in conjunction with temperature provides useful information for assessment of the potential use of this biodegradable plastic in load‐bearing applications exposed to an organic liquid. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :